(untitled) (Journal of Patan Academy of Health Sciences, 2019)
Introductions: Studies have shown inadequate use of prophylaxis for venous thromboembolism (VTE) in hospital admitted medical patients. This study aims to evaluate the use of VTE prophylaxis in admitted medical patients in a tertiary care teaching hospital. Methods: This was a cross sectional observational study for three weeks from 19 March to 8 April 2017 in patients admitted in the medical ward of Patan Hospital, Patan Academy of Health Sciences, Lalitpur, Nepal. Patient charts were reviewed for appropriate VTE prophylaxis as per modified Padua risk Assessment model. Risks of VTE, presence of bleeding risks, demographics (age, BMI), hospital stay were descriptively analysed. Results: Out of 122 patients, 81 (66.4%) were at risk of VTE. Among 81 at risk, 69 were eligible for VTE pharmacoprophylaxis with no risk of bleeding only 29 (42%) received pharmacoprophylaxis and 12 eligible for prophylaxis but with the risk of bleeding did not receive any prophylaxis. Reduced mobility was the most common indication of thromboprophylaxis in 79 (64%), followed by acute infection 50 (41%). Conclusions: There was suboptimal use of thromboprophylaxis in hospital admitted medical patients at risk of venous thromboembolism, VTE.